Crizotinib for recurring non‐small‐cell lung cancer with EML4‐ALK fusion genes previously treated with alectinib: A phase II trial. Issue 5 (20th January 2021) - Harada, Daijiro; Isozaki, Hideko; Kozuki, Toshiyuki; Yokoyama, Toshihide; Yoshioka, Hiroshige; Bessho, Akihiro; Hosokawa, Shinobu; Takata, Ichiro; Takigawa, Nagio; Hotta, Katsuyuki; Kiura, Katsuyuki; ,
Abstract: Background: The efficacy of crizotinib treatment for recurring EML4‐ALK ‐positive non‐small cell lung cancer (NSCLC) previously treated with alectinib is unclear. Based on our preclinical findings regarding hepatocyte growth factor/mesenchymal epithelial transition (MET) pathway activation as a potential mechanism of acquired resistance to alectinib, we conducted a phase II trial of the anaplastic lymphoma kinase/MET inhibitor, crizotinib, in patients with alectinib‐refractory, EML4‐ALK ‐positive NSCLC. Methods: Patients with ALK ‐rearranged tumors treated with alectinib immediately before enrolling in the trial received crizotinib monotherapy. The objective response rate was the primary outcome of interest. Results: Nine (100%) patients achieved a partial response with alectinib therapy with a median treatment duration of 6.7 months. Crizotinib was administered with a median treatment interval of 50 (range, 20–433) days. The overall response rate was 33.3% (90% confidence interval [CI]: 9.8–65.5 and 95% CI: 7.5–70.1), which did not reach the predefined criteria of 50%. Two (22%) patients who achieved a partial response had brain metastases at baseline. Progression‐free survival (median, 2.2 months) was not affected by the duration of treatment with alectinib. The median survival time was 24.1 months. The most common adverse events were an increased aspartate transaminase/alanine transaminase (AST/ALT) ratio (44%) and appetite loss (33%); one patient developed transient grade 4 AST/ALT elevation, resulting in treatment discontinuation. Other adverse events were consistent with those previously reported; no treatment‐related deaths occurred. Conclusions: Although the desired response rate was not achieved, crizotinib monotherapy following treatment with alectinib showed efficacy alongside previously described adverse events. Abstract : We evaluated the efficacy and safety of crizotinib in patients with ALK‐positive non‐small cell lung cancer refractory to alectinib. We included nine patients and stipulated an overall response rate (ORR) of 50% and a lower limit of interest of 15%. The ORR was 33.3%, failing to meet the criteria. However, the treatment showed efficacy alongside tolerable adverse effects.